Query containment in Entity SQL (Extended Abstract) - Rull, Guillem; Bernstein, Phil; Santos, Ivo; Katsis, Yannis; Melnik, Sergey; Terwilliger, James; Teniente, Ernest (Proceedings of the 2013 ACM SIGMOD International Conference on Management of Data, 2013)
We describe a software architecture we have developed for a constructive containment checker of Entity SQL queries defined over extended ER schemas expressed in Microsoft’s Entity Data Model. Our application of interest is compilation of object-to-relational mappings for Microsoft's ADO.NET Entity Framework, which has been shipping since 2007. The supported language includes several features which have been individually addressed in the past but, to the best of our knowledge, they have not been addressed all at once before. Moreover, when embarking on an implementation, we found no guidance in the literature on how to modularize the software or apply published algorithms to a commercially-supported language. This paper reports on our experience in addressing these real-world challenges.